2022
DOI: 10.1177/01945998211073705
|View full text |Cite
|
Sign up to set email alerts
|

Delphi Method Consensus on Priority Global Otolaryngology–Head and Neck Surgery Conditions and Procedures

Abstract: Objective The objective of this study was to develop an international expert consensus on priority otolaryngology–head and neck surgery conditions and procedures globally for which national health systems should be capable of caring. Study Design The Delphi method was employed via a multiround online survey administered to attending otolaryngologists in an international research collaborative of >180 otolaryngologists in >40 countries. Setting International online survey. Methods In round 1, participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 43 publications
(82 reference statements)
2
23
0
Order By: Relevance
“…Head and neck cancers account for 5.7% of global cancer- related mortality, with a significantly higher mortality burden and subsequent economic loss in LMICs compared to high-income countries (HICs) [ 33 ▪ ]. Other OHNS conditions with high global burden of disease include upper respiratory infections, cleft lip/palate, head and neck trauma, pediatric foreign body, and deep neck space infections [ 34 ▪ , 35 , 36 ▪▪ ].…”
Section: Essential Equipment and Services For Ohns Carementioning
confidence: 99%
“…Head and neck cancers account for 5.7% of global cancer- related mortality, with a significantly higher mortality burden and subsequent economic loss in LMICs compared to high-income countries (HICs) [ 33 ▪ ]. Other OHNS conditions with high global burden of disease include upper respiratory infections, cleft lip/palate, head and neck trauma, pediatric foreign body, and deep neck space infections [ 34 ▪ , 35 , 36 ▪▪ ].…”
Section: Essential Equipment and Services For Ohns Carementioning
confidence: 99%
“…In the cited Delphi consensus, a panel of globally diverse experts produced a list of 39 globally important procedures highlighting the breadth and depth of the field. 1 As regional anatomic specialists, otolaryngologists are uniquely positioned to offer medical and surgical care in a global setting to adult and pediatric patients. Despite the opportunity, implementation of formal global health care and health equity educational curriculums is currently limited in otolaryngology residency programs.…”
mentioning
confidence: 99%
“…We sincerely appreciate the letter response by Djoutsop and Kanmounye to “Design and Implementation of a Global Health and Underserved Care Track in an Otolaryngology Residency.” The letter introduces the notable work of the Global OHNS initiative and expounds on a number of key points in the original article. In the cited Delphi consensus, a panel of globally diverse experts produced a list of 39 globally important procedures highlighting the breadth and depth of the field 1 . As regional anatomic specialists, otolaryngologists are uniquely positioned to offer medical and surgical care in a global setting to adult and pediatric patients.…”
mentioning
confidence: 99%
“…This group has published seminal research on the burden of head and neck cancers 4 and identified priority interventions and diseases within global OHNS. 5 Such a collaboration may help scale the global OHNS track to other ACGME programs and expand the foreign experience to other low- and middle-income countries.…”
mentioning
confidence: 99%
“…This initiative is a research collaborative network of more than 180 otolaryngologists in more than 40 countries to understand the challenges to accessing safe, timely, and affordable OHNS care worldwide. This group has published seminal research on the burden of head and neck cancers 4 and identified priority interventions and diseases within global OHNS 5 . Such a collaboration may help scale the global OHNS track to other ACGME programs and expand the foreign experience to other low‐ and middle‐income countries.…”
mentioning
confidence: 99%